1967
DOI: 10.1136/bmj.2.5549.410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autogenous vein bypass grafts for femoro-popliteal arterial occlusion.

Abstract: Herpes Simplex Encephalitis-Evans et al. account of the sytemic use of idoxuridine in the treatment of a severe D.N.A.-virus infection, herpes simplex encephalitis.The place of idoxuridine in the chemotherapy of viral encephalitis, with or without corticosteroids, must await further trial; at least the facts of this case suggest that it may have antiviral action within the central nervous system.As the chemotherapy of virus disease. advances drugs are likely to be developed which are type-specific. Early id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1967
1967
1979
1979

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…Our results reaffirm that the reversed saphenous vein graft currently remains the best reconstructive procedure for femoropopliteal occlusive disease. Our 5-year patency is higher than that in our earlier series (Baddeley et al, 1970) and that reported by De Weese and Robb (1977) but it remains lower than in some other series (Darling et al, 1967;Cutler et al, 1976).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Our results reaffirm that the reversed saphenous vein graft currently remains the best reconstructive procedure for femoropopliteal occlusive disease. Our 5-year patency is higher than that in our earlier series (Baddeley et al, 1970) and that reported by De Weese and Robb (1977) but it remains lower than in some other series (Darling et al, 1967;Cutler et al, 1976).…”
Section: Discussioncontrasting
confidence: 58%
“…'excellent' with normal popliteal and tibial vessels; 'good' when minimal disease of the popliteal and tibial arteries was present ; 'moderate' with 'scalloping' of the popliteal artery and occlusion of one of the three main calf arteries or narrowing of the others; 'poor' when two or all three calf arteries were occluded (Baddeley et al, 1970). The patency rates, summarized in Table V, for good and moderate run-off were satisfactory, with 5-year patency rates of 75 per cent.…”
Section: R P Grimley Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Dyspepsia was investigated because of the dangers associated with anticoagulant therapy in peptic ulceration and because of the age of the patients concerned; evidence of malignancy was also routinely sought. The surgical technique for reversed autogenous vein bypass graft remains as we previously reported (Baddeley et al, 1967). At the follow-up examination grafts were designated successful if the graft itself or pedal pulses were palpable.…”
Section: Patients Studiedmentioning
confidence: 99%
“…Aortocoronary bypass surgery is increasingly performed to relieve symptoms from coronary artery disease (1)(2)(3)(4)(5)(6). Evaluation for surgery is dependent on the findings noted at selective coronary angiography (3,(7)(8)(9)(10). Several attempts at defining the relationship between operability of the vessel, the flow obtained at the time of surgery and the future patency of the graft have been made (7)(8)(9).…”
mentioning
confidence: 99%